Noun phrase complexity in English - Berlage, Eva (Cambridge : Cambridge University Press, 2014)
This book explores noun phrase complexity in English, showing that it is best accounted for both by a linear and a hierarchical parameter: its length and its type of postmodifier(s). The study is methodologically unique in that it combines univariate and multivariate analyses in an investigation of four different syntactic variables. Drawing on more than three billion words of British and American data, Eva Berlage shows that the length and the structure of the NPs, along with language-external factors such as the regional variety of English, work as powerful determinants of the variation. On a theoretical level, the book reveals that the structural complexity of NPs cannot be sufficiently captured by (phrasal) node counts but that we need to incorporate the degree to which NPs are sentential. The book is designed for researchers and students interested in syntax, language variation, sociolinguistics, structural complexity and the history of English.
1. Introduction; 2. The variationist framework; 3. Methodology I: defining the syntactic complexity of NPs; 4. Methodology II: modes of data presentation, statistical procedures and electronic corpora; 5. Optional verb phrases in topic-restricting as far as constructions; 6. Word order variation involving the collocations take prisoner, hold prisoner and take hostage, hold hostage; 7. Word-order variation involving pre- and postposed notwithstanding; 8. Infinitival variation following help; 9. NP-complexity and change; 10. Conclusion and future directions.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: English language -- Noun phrase; English language -- Syntax